(untitled) (East West Medical College Journal, 2024)
Background: Coronavirus disease (COVID-19) is an irresistible illness caused by the SARS-CoV-2 infection. Most individuals who drop wiped out with COVID-19 will involvement gentle to direct side effects and recoup without uncommon treatment. Some will become seriously ill and require medical attention. However, it is preventable through obeying some measures of personal hygiene. Methods: This descriptive cross-sectional study was conducted to determine COVID-19 status among people of different strata in Uttara and Savar. A total of 1200 conveniently selected respondents were interviewed face-to-face using a semi-structured questionnaire. Results: Mean age was 38.59 years with standard deviation ±14.117 years. Majority (63.33%) were male. Among them 20.7% were housewives, 11.5% were students, 15.3% were businessmen and 9.3% were service holders. Most (98.6%) of the respondents mentioned to know about pandemic situation of COVID-19. Among the respondents 207 (17.3%) suffered from COVID-19. Among those who suffered from COVID-19 (207), 157 performed test for COVID-19 and was positive. The other 50 did not perform test and only assumed to be suffering from COVID-19 as they had symptoms. On the other hand, 993 respondents mentioned of not suffering from COVID-19. Among them, 803 had no symptom and 190 underwent COVID-19 test and were negative. Proportion of suffering from COVID-19 was found high among the doctors (64.1%), service holders (22.5%), students (21.7%) and teachers (21.1%). Conclusion: Measures to be undertaken to create awareness among the people to abide by the health rules so that we can reduce the incidence of COVID 19. EWMCJ Vol. 12, No. 1&2, January-July 2024: 80-87